A history of English literature - Alexander, Michael, 1941- (Palgrave Macmillan, 2013)
"Traces the development of one of the world's richest literatures from the Old English period through to the present day. The narrative discusses a wide range of key authors but never loses its clarity or verve. This current revised edition provides a full final chapter on the contemporary scene with more on genres and the impact of globalization."
Předchozí vydání: 2007
Keywords: dějiny anglické literatury; history of English literature; přehledy; surveys